Innovation activity in South Africa: Measuring the returns to R&D - Andre Steenkamp; Mark E. Schaffer; Wayde Flowerday; John Gabriel Goddard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Improvements in productivity are necessary to effectively increase economic growth in the long term. The literature emphasizes a positive correlation between firm-level innovation and productivity gains. It is unsurprising, then, that policy makers and researchers widely acknowledge that innovation is one of the major drivers of productivity growth, and is therefore of critical importance to the competitiveness and growth of firms. Research and development (R&D) expenditure is used extensively as a proxy for innovation in the literature. Here, we use a production function approach to estimate the return to R&D in South African manufacturing firms for the period 2009-2014 using South African firm-level data. We find that the return to R&D in South African manufacturing firms is high compared to OECD countries. This analysis has been undertaken several times for OECD countries, but far less frequently for non-OECD countries. These findings therefore are not just novel for South Africa, but for the development economics literature more generally, and raise important insights for innovation policy in South Africa.
Keywords: O30; O38; C23; C81; D24; 330; innovation; returns to R&D; total factor productivity; technological change